2020
DOI: 10.1021/acs.jced.0c00074
|View full text |Cite
|
Sign up to set email alerts
|

Separation Process of Nisin Using Aqueous Two-Phase Systems: A New Approach Featuring Nanoparticles

Abstract: In this study, to improve the efficiency of an aqueous two-phase system (ATPS), a different scenario has been proposed. To this purpose, an endeavor has been undertaken to find a nanoparticle suitable for designing a process of favorable economic separation as well as to unravel the mechanism of the partitioning of nisin along with nanoparticle. First, the capabilities of several different nanoparticles were assessed. These nanoparticles were regarded as additives apt to improve nisin partitioning in the ATPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…They showed that the modified system enhanced the partition coefficient of vanillin by 127%. Rahbari et al 10 conducted a study to evaluate a group of nanoparticles for their ability to partition nisin in ATPS containing PEG and phosphate-based salt. The study showed that the presence of nanoparticles increased the partition factor of nisin 8-fold compared to the ATPS with no nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that the modified system enhanced the partition coefficient of vanillin by 127%. Rahbari et al 10 conducted a study to evaluate a group of nanoparticles for their ability to partition nisin in ATPS containing PEG and phosphate-based salt. The study showed that the presence of nanoparticles increased the partition factor of nisin 8-fold compared to the ATPS with no nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the modified system enhanced the partition coefficient of vanillin by 127%. Rahbari et al . conducted a study to evaluate a group of nanoparticles for their ability to partition nisin in ATPS containing PEG and phosphate-based salt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation